2012
DOI: 10.1088/0031-9155/55/5/1203
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic programming approach to adaptive fractionation

Abstract: Abstract. We conduct a theoretical study of various solution methods for the adaptive fractionation problem. The two messages of this paper are: (i) dynamic programming (DP) is a useful framework for adaptive radiation therapy, particularly adaptive fractionation, because it allows us to assess how close to optimal different methods are, and (ii) heuristic methods proposed in this paper are near-optimal, and therefore, can be used to evaluate the best possible benefit of using an adaptive fraction size.The ess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Using imaging information obtained between treatment days, dynamic optimization models have been developed to adaptively compensate for past accumulated errors in dose to the tumor ( [12,10,11,49]). There also has been work on online approaches which adapt the dose and treatment plan based on images obtained immediately prior to treatment ( [30,9,24,23,14,25,45]).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Using imaging information obtained between treatment days, dynamic optimization models have been developed to adaptively compensate for past accumulated errors in dose to the tumor ( [12,10,11,49]). There also has been work on online approaches which adapt the dose and treatment plan based on images obtained immediately prior to treatment ( [30,9,24,23,14,25,45]).…”
Section: Related Workmentioning
confidence: 99%
“…The opportunity to then adapt the treatment to the observed data, rather relying on a model, becomes a possibility. While previous works have investigated using imaging technology to select dose fractions ( [30,9,24,23,14,45]), they have not done so to counter accelerated repopulation. While the problem in this paper can be seen as a special case of the general one presented in [25], the effect of tumor proliferation, which is our main focus, was not analyzed therein.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…They concluded that the larger fractional (prescription) dose is optimal when there is a larger distance between the tumor and OAR. 48 They showed that there is potential to decrease the dose to the OAR using ART if there is a large variation in the distance between the tumor and OAR during a treatment course. In this case, the state of the system is the distance between the tumor and OAR subject to uncertainty, thereby requiring a motion probability distribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, in principle inter-fraction tumor motion can even be exploited, that is, a better treatment quality may be achieved in the presence of motion compared to a static patient geometry. Adaptive fractionation (AF) (Chen et al 2008, Ramakrishnan et al 2012 is one approach to exploit inter-fraction motion. In this approach, a treatment plan is not only adapted to the daily patient geometry, but also the dose delivered to the tumor in each fraction is modified: the dose is increased on favorable treatment days, i.e.…”
Section: Introductionmentioning
confidence: 99%